2016
DOI: 10.1002/anie.201511555
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis by Networks of Cooperative Hydrogen Bonds: Enantioselective Direct Mannich Addition to Preformed Arylideneureas

Abstract: The concept of noncovalent organocatalysis by means of networks of cooperative hydrogen bonds (NCHB organocatalysis) has been explored. Arylideneureas were chosen as ideal substrates because of their powerful donor-acceptor properties. We have examined their uncatalyzed, direct Mannich reaction with acetoacetates in comparison with that catalyzed by a number of salan derivatives capable of providing a network of cooperative hydrogen bonds. Catalyst D [(R,R)-N,N'-bis(salicyl)cyclohexane-1,2-diamine] was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…and Ooi et al ,. in which unprecedented organocatalytic capacities of some hydrogen bond networks have been reported (Figure ), we demonstrated that the network of cooperative hydrogen bonds present in salan organocatalysts was capable of driving the direct Mannich addition of acetoacetates (NuH) to preformed arylideneureas (E) in an enantioselective, enzyme‐like manner (Scheme ) and eventually, after acid treatment, gives rise to Biginelli DHPMs …”
Section: Figurementioning
confidence: 71%
See 4 more Smart Citations
“…and Ooi et al ,. in which unprecedented organocatalytic capacities of some hydrogen bond networks have been reported (Figure ), we demonstrated that the network of cooperative hydrogen bonds present in salan organocatalysts was capable of driving the direct Mannich addition of acetoacetates (NuH) to preformed arylideneureas (E) in an enantioselective, enzyme‐like manner (Scheme ) and eventually, after acid treatment, gives rise to Biginelli DHPMs …”
Section: Figurementioning
confidence: 71%
“…Actually, best results were obtained when 2 equivalents of TMG were employed, thus leading to enantioselectively enriched HHPMs 2 in good overall yield with a ≈9:1 diasteromeric ratio and a quite high enantiomeric excesses (Scheme ). The relative stereochemistry of the major diastereomer was inferred from their ROESY spectra, and its absolute (4 R , 5 R , 6 S ) stereochemistry deduced from that of the corresponding DHPMs 3 that result by treatment of 2 with aqueous acid . The ROESY spectra also revealed that the minor stereoisomer was the (4 S , 5 R , 6 S ) epimer.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations